1995
DOI: 10.1093/carcin/16.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk of heterocyclic amines in cooked foods: an analysis and implications for research

Abstract: Heterocyclic amines (HAs) are formed as pyrolysis products during the cooking of meats/fish. These substances are potent mutagens in the Ames/Salmonella assay and are also carcinogens in laboratory animals. In order to assess the magnitude of the cancer risk posed by their presence in the US diet, we estimated the average intakes of HAs, based on analyses of the concentrations of HAs in cooked foods and data from a dietary survey of the US population and quantified the cancer potencies of the individual compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
283
3
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(294 citation statements)
references
References 0 publications
7
283
3
1
Order By: Relevance
“…Mutagens and carcinogens are formed during cooking at high temperature [37]. To be more specific, fried, barbecued or flamebroiled meats have a higher mutagenic activity than stewed, baked, boiled or steamed meat [2]. Fried meat was associated with breast cancer in a case-control study from Uruguay [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutagens and carcinogens are formed during cooking at high temperature [37]. To be more specific, fried, barbecued or flamebroiled meats have a higher mutagenic activity than stewed, baked, boiled or steamed meat [2]. Fried meat was associated with breast cancer in a case-control study from Uruguay [3].…”
Section: Discussionmentioning
confidence: 99%
“…A recent pooled analysis of eight prospective cohort studies did not find an association between intake of total meat, red meat or white meat [1]. However, if meat plays a role in the etiology of breast cancer this could be through the formation of mutagens and/or carcinogens, such as heterocyclic amines (HA), during high temperature cooking of meat [2]. Consumption of well-done meat has been associated with an increased human breast cancer risk in some but not all epidemiological studies [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several studies have reported positive [4][5][6] and negative [7][8][9] results on the association between meat intake and PCa. Heterocyclic amines formed by the reaction of amino acids, creatine and sugar during high-temperature cooking of meat and fish produce tumors in experimental animals 10,11 including prostate tumors in the rat. 12 Cytochrome P-450 and N-acetyltransferases (NAT), respectively, catalyzed N-hydroxylation and O-acetylation are believed to be pivotal to the activation of heterocyclic amines.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary HA exposures from cooked -food sources typically include exposures dominated by five compounds: 2 -amino-9H -pyrido [ 2,3-b ]indole ( A C ), 2 -amino-3-methylimidazo [4,5 -f ]quinoline (IQ ), 2 -amino-3,4,8 -trimethylimidazo [4,5 -f ]quinoxaline (DiMeIQx), MeIQx and PhIP Sugimura et al, 1986Sugimura et al, , 1988Felton and Knize, 1990a,b;Layton et al, 1995 ). Meat type, cooking duration and cooking temperature are among factors known to influence the extent to which these (and other ) HAs form in cooked meats ( Knize et al, 1994;Skog et al, 1995;Sinha et al, 1998a,c;Keating et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meat type, cooking duration and cooking temperature are among factors known to influence the extent to which these (and other ) HAs form in cooked meats ( Knize et al, 1994;Skog et al, 1995;Sinha et al, 1998a,c;Keating et al, 1999 ). Estimates of population -average dietary HA intake vary considerably, ranging from $1 to >20 ng/kg /day (Layton et al, 1995;Thomson et al, 1996;Augustsson et al, 1997;Byrne et al, 1998). Reasons for this variability include different assignment of HA concentrations to cooked meats consumed by the public, differences in estimated meat consumption, and differences in assumed cooking practices ( Keating et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%